Effect of intranasal administration of Erigeron annuus and Carthamus tinctorius extracts in a rat model of olfactory dysfunction induced by 3-methylindole. - Myeongguk Jeong; Hyeokjin Kwon; Yeeun Kim; Kyung-Yae Hyun; Yeongdon Ju; Go-Eun Choi; Chulhun L Chang (PLoS ONE)
There are many factors that can cause olfactory dysfunction, including upper respiratory tract viral infections, non-inflammatory respiratory diseases, trauma, and current treatments such as medications and surgery can have adverse effects and may not respond. Therefore, we aimed to develop a natural product-based adjunctive treatment strategy for olfactory dysfunction that is safe and has minimal adverse effects. We investigated the effects of extracts from Erigeron annuus and Carthamus tinctorius, which have demonstrated anti-apoptotic, neuroprotective, and anti-inflammatory activities, on 3-methylindole-induced olfactory dysfunction. A 3-methylindole-induced olfactory dysfunction model rat was established and olfactory dysfunction was treated with intranasal administration of Erigeron annus extract (EAE) and Carthamus tinctorius extract (CTE) or their combination. After 3 weeks, alterations in food-finding tests and OMP expression in olfactory bulb and olfactory epithelium were assessed. Comparing the food finding test, the EAE + CTE group had a significant decrease in food finding time compared to the vehicle group. IHC and Western blot analyses showed that OMP expression in the olfactory bulb was significantly increased in the EAE + CTE group compared to the vehicle group. Western blot analysis of olfactory epithelial tissue also showed a significant increase in OMP expression. Intranasal administration of EAE + CTE alleviated 3-methylindole-induced olfactory dysfunction.